Comparison of cholinesterase inhibitor safety in real‐world practice. Issue 1 (1st January 2019) - Carney, Greg; Bassett, Ken; Wright, James M.; Maclure, Malcolm; McGuire, Nicolette; Dormuth, Colin R.
Abstract: Introduction: Cholinesterase inhibitors (ChEIs) are widely used to treat mild to moderate Alzheimer's disease and related dementia. Clinical trials have focused on placebo comparisons, inadequately addressing within‐class comparative safety. Methods: New users of ChEIs in British Columbia were categorized into five study cohorts: low‐dose donepezil, high‐dose donepezil, galantamine, rivastigmine patch, and oral rivastigmine. Comparative safety of ChEIs assessed hazard ratios using propensity score adjusted Cox regression. Results: Compared with low‐dose donepezil, galantamine use was associated with a lower risk of mortality (adjusted hazard ratio: 0.84, 95% confidence interval: 0.60–1.18), cardiovascular serious adverse events (adjusted hazard ratio: 0.78, 95% confidence interval: 0.62–0.98), and entry into a residential care facility (adjusted hazard ratio: 0.72, 95% confidence interval: 0.59–0.89). Discussion: Given the absence of randomized trial data showing clinically meaningful benefit of ChEI therapy in Alzheimer's disease, our study suggests preferential use of galantamine may at least be associated with fewer adverse events than treatment with donepezil or rivastigmine. Highlights: Galantamine was associated with fewer adverse events than donepezil or rivastigmine. Galantamine users experienced longer independent living. The 3‐year risk of cardiovascular events and mortality was lowest with galantamine.